Radiation induced color centers in cerium-doped and cerium-free multicomponent silicate glasses - 傅鑫杰 宋力昕 李家成 (Journal of rare earths, 2014)
The effect of doped cerium on the radiation-resistance behavior of silicate glass was investigated in our work. The ultraviolet-visible absorption spectra and electron paramagnetic resonance（EPR） spectra were obtained after the cerium-rich and cerium-free multicomponent silicate glasses（K509 and K9） were irradiated by gamma rays with a dose range from 10 to 1000 kGy. The results showed that E’ center, oxygen deficient center（ODC） and non-bridging oxygen hole center（HC1 and HC2） were induced in K9 and K509 glasses after radiation. The concentrations of all color centers presented an exponential growth with the increase of the gamma dose. Moreover, the concentration of HC1 and HC2 in cerium-doped K509 glass was much lower than that in cerium-free K9 glass at the same dose of radiation, which could be attributed to the following mechanism： Ce3＋ ions capturing holes then forming Ce3＋＋ centers inhibited the formation of hole trapped color centers（HC1 and HC2） and Ce4＋ ions capturing electrons to form Ce3＋ centers suppressed the formation of electron trapped color centers like E’ center.